Application of the Five-Finger Hypnosis Relaxation Technique in Nursing Care for Hypertensive Patients - Arlies Zenitha Victoria; Davina Rahma Dania Putri Rosiany; Dela Ayu Kurniawati; Desika Indrawati; Desita Triana Adila; May Wulansari (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Hypertension is often referred to as the